The full stack web development - Traversy, Brad (Packt Publishing, 2017)
"With the fast paced nature of technology, developers can no longer become experts in aspects of development, but now must learn the entire process of development from design to actual deployment. This has introduced a new role for developers - Full Stack Developers. However, resources to become a Full Stack Developer are limited and only offer sections or just random technologies that you must learn and combine on your own. So, we introduced this course that compiles all technologies in perfect sync to help developers transition from a simple developer to become a Full Stack Developer. Starting from front-end development, the learner will slowly progress to become to other aspects of development including back-end, database, debugging, version control and other essential technologies that are helpful for a developer."--Resource description page